? RESIDUAL EFFECT OF STOMP 330E (PENDIMETHALIN) ON THE SUCCEEDING CROPS - ZAKI, M. S.; SHAH, S. M; MUHAMMAD, D.B. (Biological Sciences - PJSIR, 1995)
The field investigations were carried out for three consecutive years from 1984-85 to 1986-87 at the Agronomic Research Area, Central Cotton Research Institute, Multan to see the residual effect of Stomp 330 (Pendimethalin) [N-( l-ethylpropyl)-3, 4-dimethyl-2, 6-dinitrobenzenamine] at 1.2 Kglha on different crops following its treated and untreated plots in cotton. From three years average it was concluded that there were no significant differences between Stomp 330E treated and untreated plots of the succeeding crops. However, Stomp 330E treated plots gave higher number of seedlings/m’, plant height and grain yields Kg/ha than untreated plots. Thus the use of Stomp 330E for weed control in cotton was safe and had no residual effects on the succeeding crops viz. wheat, maize, sunflower; soybean and mung.